Pedagogia histórico crítica e educação histórica: contribuições para o ensino de história nas etapas 7,8 e 9 do EJA - Adam, Maurício José (2016)
This work consists of a proposal for a workshop built from a survey among students of stage 7, 8 and 9 of the Youth and Adult Education in a public school of Rio Grande do Sul state. The aim of this research was to analyze the interest of students by the knowledge of history as a curricular component and the contributions of knowledge produced by this component in the daily lives of students and their guidance practices in time. Through the collection of the information, it was possible to identify that the interest of students by historical knowledge is mostly of simple curiosity, also it was showed that students do not understand the present as a result of past events. Based on these results it was possible theoretically organize a workshop for teachers that includes the concepts of historical critical pedagogy built by Dermeval Saviani and Historical Education by Jörn Rüsen aiming the professional training of teachers through the theoretical prerogatives mentioned before. This practice is based on the possibility and relevance to improve discussions about the historical knowledge produced and disseminated in the school environment, in this case, frequented by young people and adults.